Pengaruh unsafe action terhadap kecelakaan kerja pada pekerja konstruksi di PT. DAP Perumahan Citra Land Bagya City Kota Medan - Panjaitan, Sonatha Sapta Utami; Silalahi, Marlinang Isabella (Program Studi Magister Kesehatan Masyarakat Universitas Prima Indonesia, 2019)
A work accident is any unsafe act or condition that can result in a loss. Work accident is an event or unwanted event that is detrimental to humans, damage property or loss of process. The Social Security Organizing Agency (BPJS) in North Sumatra, stated in the Medan Belawan area there were 1,094 cases, Tanjung Morawa had 1,218 cases and Medan Kota had 484 cases, with an average of around 15 work accident cases each day. This type of research used in this study was an observational study with a cross-sectional method. The population of this research is construction workers in the construction of Citra Land Bagya City Medan, as many as 30 respondents. The sample in this study were all construction workers housing Citra Land Bagya City Medan. The sampling technique in this study was a total sampling of 30 respondents. The results of this study were statistically tested using the chi square test with a 95% confidence level. The results showed that there was a relationship between the use of PPE to work accidents with a p value of 0.031 <0.05. Then there is no relationship of knowledge with the occurrence of workplace accidents with a p value of 0.282> 0.05 and there is no relationship between attitude and the occurrence of workplace accidents with a p value of 0.543> 0.05). It is recommended that workers be disciplined in using PPE when working, and supervision of the use of PPE is increased so that optimal safety and health are guaranteed.